SISTEM PENDUKUNG KEPUTUSAN PENERIMA BEASISWA MENGGUNAKAN METODE WEIGHTED PRODUCT - Turaina, Rifa; Karfindo, Karfindo (Ensiklopedia of Journal, 2021)
Scholarship is one of the school programs to help ease the burden on parents of students to ease the burden of education costs for students. SMP N 2 Sungayang, there is also a scholarship program aimed at students, both deserving and underprivileged and of course based on predetermined criteria. To help schools determine students who are eligible to receive scholarships, a Decision Support System (SPK) can be used, where one of the decision methods that can be used is the Weighted Product (WP) method. Weighted Product is a method used to find several students from a number of students with certain criteria. The result of this research is an SPK application that can assist the school in determining who is entitled to receive a scholarship based on predetermined criteria and weights.